2017
DOI: 10.4085/1062-6050-52.12.22
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Performance Characteristics Related to Unintentional Musculoskeletal Injury in Special Forces Operators: A Prospective Analysis

Abstract: Context: Seventy-seven percent of musculoskeletal injuries sustained by United States Army Special Forces Operators are preventable. Identification of predictive characteristics will promote the development of screening methods to augment injury-prevention programs.Objective: To determine physical and performance characteristics that predict musculoskeletal injuries.Setting: Clinical laboratory. Patients or Other Participants: A total of 95 Operators (age ¼ 32.7 6 5.1 years, height ¼ 179.8 6 6.9 cm, mass ¼ 89.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…Interestingly, although not significant, in the pretesting the non-injured group had the ‘average’ BMI compared with participants who were injured in the first half of the course (had higher BMI) and compared with participants who were injured in the second half of the course (with lower BMI). Similar to our results, Heebner et al 23 and Teyhen et al 12 found no difference in BMI in soldiers who sustained an injury and those who did not. Looking at the army literature, there is no consistency considering the relation between high/low BMI and injuries.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, although not significant, in the pretesting the non-injured group had the ‘average’ BMI compared with participants who were injured in the first half of the course (had higher BMI) and compared with participants who were injured in the second half of the course (with lower BMI). Similar to our results, Heebner et al 23 and Teyhen et al 12 found no difference in BMI in soldiers who sustained an injury and those who did not. Looking at the army literature, there is no consistency considering the relation between high/low BMI and injuries.…”
Section: Discussionsupporting
confidence: 92%
“…It was suggested that a higher BMI may have a protective effect against injury, due to the greater absolute amounts of muscle among soldiers with higher BMI that enable those soldiers to cope better with load-carrying tasks than their lighter counterparts 11 24. In contrast, Heebner et al 23 reported that army operators who sustained a spinal injury had a significantly greater BMI than those who did not. Additionally, several studies of military trainees have demonstrated either a J-shaped or a bimodal relationship between BMI and injury risk (high injury risk at the high and low extremes of BMI, and lowest among those with ‘average’ BMI) 21.…”
Section: Discussionmentioning
confidence: 99%
“…One additional text was identified by a content expert 17. Following a full-text review, 21 studies were retained for analysis 17–37. The main reason for study exclusion was due to other occupation types in the sample population, and the results were not reported separately to provide data exclusive to a SOF population.…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies reported injury anatomical locations. Three studies grouped their analysis by body regions of which the lower extremity and spine were the most common regions affected 25 32 34. Fourteen studies analysed by specific body parts of which the ankle, knee and lumbar region were the most frequently affected sublocations.…”
Section: Resultsmentioning
confidence: 99%
“…Arms and legs can be compared with their contralateral to define deficits or imbalances but, unlike the extremities, the trunk does not have this possibility, which makes it difficult to find parameters of normality or reference. Trunk strength has been related to injury prevention [ 25 , 26 ], which is why it plays an important role in the functional evaluation of people or athletes [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%